Beta-glucans from biomass of plant and microbial origin - N. Yu. Sharova; B. S. Manzhieva; A. A. Printseva; T. V. Vybornova (Пищевые системы, 2019)
The aim of the present study is to explore the transformation of (1→3)(1→4)-β-D-glucans of rye biomass by Aspergills niger and accumulation of (1→3)(1→6)-β-D-glucans in the microbial cell wall.Biomass from rye grain was obtained as a result of enzymatic hydrolysis of grain grinding of Omsk region of non-standard quality with grain impurity content of 45 ± 2 % by preparations (1→4)-β-glucanolytic, (1→3)-β-glucanolytic, (1→4)-xylanolytic and (1→4)-amylolytic action. Fermentation of hydrolysates, sucrosemineral and molasses medium by A. niger was carried out by a batch process under aerobic conditions. Determined the content of β-glucans, amino-nitrogen, glucose, disaccharides in grinding grain rye, rye biomass, the biomass of A. niger, the supernatants by colorimetric methods. Determination of chitin in biomass and qualitative determination of chitosan in supernatants of hydrolysates was carried out using chitosan sulfate sample and subsequent microscopy.The results of the research showed that (1→3)(1→4)-β-D-glucans in grain grinding are 10.2 ± 0.2 % in terms of dry matter, which exceeds the content of polysaccharide in the grain of standard quality by 1.5 – 3 times. In rye biomass revealed their smaller amount, 6.4 ± 0.5 %, apparently, due to the action of (1→4)and (1→3)-β-glucanase, (1→4)-xylanase and (1→4)-amylase. In microbial mass A. niger content of (1→3)(1→6)-β-Dglucans were at the level of 21.7 ± 0.7 %.On the basis of the obtained results, it was concluded that it is possible to use rye grain of non-standard quality, with a high content of grain impurities and a low proportion of starch polysaccharides, as a source of β-glucancontaining substrate for biosynthesis (1→3)(1→6)-β-D-glucans by A. niger having advantages over (1→3) (1→4)-β-D-glucans of plant origin. They are functionally more active and have a wide range of applications, namely as food additives in the manufacture of a wide range of products: for the enrichment of fibers, increasing the shelf life of products due to its water-binding properties, as thickeners, emulsifying and fat-reducing microingredients, stabilizers of creamy emulsions, textureformers, flavor enhancers.